Peripheral Cemento Ossifying Fibroma – A Case Report - Rane Jaai; Jasmin winnier J.; Bhatia Rupinder (Journal of Dentistry And Oral Implants, 2016)
Introduction: Cemento-ossifying fibroma is is a reactive lesion arising from the soft tissues (gingiva). Case report: A 13-year-old boy presented with the complaint of lump in mandibular right posterior region on the lingual side since a month. The patient presented no symptoms and had no medical history of interest. The lesion was excised and submitted for histopathological evaluation, which gave a diagnosis of peripheral cemento-ossifying fibroma. Discussion: Periheral Cemento-ossifying fibromas are slow-growing lesions, and are more frequent in women between the second and third decades of life. Although the underlying cause is not known, there have been reports of the lesion developing after irritation/ trauma in the concerned area. Due to the good delimitation of the tumor, surgical removal and curettage is the treatment of choice.
Keywords: Peripheral Cemento-ossifying fibroma